Lessons from delivering as one: options for UN member states - Silke Weinlich; Urs Zollinger (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
Since 2007, the UN development system has experimented with new approaches to enhance its coherence, efficiency and effectiveness in eight pilot countries. Similar to other international processes aiming to increase the effectiveness of aid and development policy through coordination, the results are mixed. Some benefits could be reaped, although the pilot initiative Delivering as One (DaO) has demonstrated that there are clear limits to what can be achieved with voluntary coordination within existing mechanisms and accountability structures. The lessons learned from DaO provide an important input for the on-going negotiations in the UN General Assembly. In autumn 2012, Member States will formulate guidance and directions for the UN development system for the next four years, the so called Quadrennial Comprehensive Policy Review (QCPR). The QCPR provides a crucial opportunity for Member States to adapt the UN development system to the changing landscape of global development cooperation. In principle, they have four options: States could agree that the pilots provided interesting insights, but that DaO should not be pursued further. States could decide that DaO is a valuable new approach that programme countries can adopt on a voluntary basis, yet fail to give clear and decisive guidance to the UN agencies to overcome the identified obstacles. States could combine their support for DaO as a voluntary option with imperative directives to UN agencies by – among other things – replacing the current consensus- based decision making at the country level with an Arbitrator System . In such a system, the Resident Coordinator would have ultimate authority, for instance with regard to allocating tasks and resources among agencies. In parallel, a more reliable and sustainable funding mechanism would be put into place . States could agree that the DaO pilots were too modest a reform attempt, and decide to tackle the challenges of the UN development system in a more fundamental way and completely redesign the UN structure and accountability system at the country level with for example a small number of Operational Lead Agencies . Only options (3) and (4) would clearly be a departure and count as an attempt to actively address the looming threat of a marginalised UN development system that is irrelevant to developing countries' needs and to the provision of global public goods. UN Member States may have different views on the future organisation and objectives of UN operational activities, but they should agree that it is their responsibility to decide on a reform path. If the reform is left to the UN agencies – like in the DaO pilot exercise – reform would not only advance very slowly, but also within narrow boundaries and with high transaction costs. Therefore, Member States must step up and truly empower the Resident Coordinator by setting up an Arbitrator System. They must install funding mechanisms that both provide reliable funding and incentivise cooperation among UN agencies. And they should explore the Operational Lead Agencies model, which provides a bold solution to the highly fragmented accountability within the UN development system.
Keywords: 330; Regionale + globale + transnationale Governance; Wirksamkeit und Evaluierung; Aufstrebende Mächte